Factor cluster analysis of Qingdao Port logistics competitiveness - Wei Xu; Xiaohan Gong (Logistics, 2020)
In order to make clear the positioning of the port logistics competitiveness of Qingdao Port among the major coastal ports in China, recognize the development level and shortcomings of its own port, and promote the enhancement of its own port logistics competitiveness, this paper uses the factor analysis method and fuzzy equivalence relationship clustering method to select 17 evaluation indicators from the two dimensions at the port hardware level and software level, respectively. Based on the relevant index data of nine major coastal ports in China including Qingdao Port from 2019, this paper makes a comparative analysis on the competitiveness of Qingdao Port in major coastal port groups in China. The results reflect the differences in the competitiveness of port logistics, and find the weaknesses of Qingdao Port in the strength of the port logistics industry, port transport conditions, etc., so as to improve and enhance the competitiveness of port logistics, such as increasing the proportion of port fixed investment, and speeding up the adjustment of transport structure.
Keywords: 650; competitiveness; factor analysis; fuzzy clustering; port logistics